The Pragmatic Functions of ‘I Don't Think’ and ‘I Think + Not’ - Sabet, P.; Zhang, Grace (Routledge, 2018)
This study provides an account of the pragmatic functions of the stance markers ‘I don't think’ and ‘I think + not’, based on naturally-occurring L1 (American English speakers) and L2 (Chinese and Persian English speakers) classroom corpora. Of the four pragmatic functions, emphatic, evaluative, tentative and mitigating, evaluative (informative) is used the most and mitigating (interpersonal) is used the least. The two expressions can also be explained in terms of fluidity and stretchability. There is a certainty degree of fluidity in the use of ‘I don't think’ and ‘I think + not’; they may perform more than one function simultaneously in the same utterance. Stretchability is manifested in that from the default evaluative function, the expressions stretch upwards (strengthening) to the emphatic and downwards (softening) to the tentative and mitigating functions.